PENGARUH KONEKSI POLITIK, INTENSITAS MODAL, DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - REZA PUTRI UTAMI; SUGIARTO PRAJITNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study was conducted with the aim of analyzing and obtaining empirical evidence regarding the influence of profitability, company size, institutional ownership, political connections, audit committee, leverage, and capital intensity on tax avoidance, which is proxied by the cash effective tax rate (CETR). The study used manufacturing companies that were consistently listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023 as the research object. The purposive Sampling method was used as the data collection technique, resulting in a sample of 72 companies with a total of 216 company samples during period 2021-2023. Data processing for the sample was conducted using the Statistical Package for the Social Sciences (SPSS) Version 25..A multiple linear regression statistical analysis method was employed to test the influence of independent variable on the dependent variables. The results of multiple linear regression analysis for hypothesis testing indicate that probability, company size, institutional ownership, political connections, audit committee, leverage, and capital intensity do not influence tax avoidance.